2009
DOI: 10.3181/0902-rm-80
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Connexin 43 Hemichannels Reduces Neointima Formation After Vascular Injury by Inhibiting Proliferation and Phenotypic Modulation of Smooth Muscle Cells

Abstract: Connexins 43 (Cx43) plays a key role in neointimal formation after vascular injury, but the mechanism still needs to be further explored. We hypothesized that the gap junction-dependent function of Cx43 to mediate intercellular communication has a crucial role in the development and progression of vascular diseases. The effect of intercellular communication mediated by Cx43 hemichannels on neointimal formation after vascular injury was investigated. Cx43 was overexpressed or knockdown in rat vascular smooth mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 41 publications
2
27
1
Order By: Relevance
“…In support of this idea, recent studies have highlighted a potential role for connexin 43 hemichannels in regulating vascular smooth muscle cell phenotype in response to balloon injury and other mitogenic stimuli. 41,42 Further, our data suggest that the presence of both Wnt3a and TGF-b may have an additive effect on cell phenotype, as we observed their combined effects to be much greater than the effect of either protein individually.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In support of this idea, recent studies have highlighted a potential role for connexin 43 hemichannels in regulating vascular smooth muscle cell phenotype in response to balloon injury and other mitogenic stimuli. 41,42 Further, our data suggest that the presence of both Wnt3a and TGF-b may have an additive effect on cell phenotype, as we observed their combined effects to be much greater than the effect of either protein individually.…”
Section: Discussionmentioning
confidence: 56%
“…28 It has previously been reported that connexin 43 expression is upregulated in smooth muscle cells in response to injury in rodent models and in early human atherosclerosis, situations in which elevated Wnt signaling has been reported 7,14 and in which increased extracellular matrix synthesis is well documented. 3,38 Reducing connexin 43 expression has been shown to inhibit lesion development in rodent models of atherosclerosis and acute vascular injury, [39][40][41] suggesting potential pro-atherogenic functions for gap junction communication. Our data suggest Wnt3a increases the expression of connexin 43 in vascular smooth muscle cells, and this increase in connexin 43 expression is associated with increased intercellular communication and matrix synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, the baseline diameter remained constant throughout our study, indicating that the decrease in FMD was not the result of a change in resting tone. Thus this attenuation effect of CBX on FMD could be attributed to the blockade of endothelial gap junctions (37).…”
Section: Discussionmentioning
confidence: 99%
“…In some experiments CBX did not alter connexin 43 hemichannel (Cx43Hc) conductance [125]. In another study CBX has been proven to disrupt hemichannel packing and aggregation in vivo [126], and CBX acts indirectly by intercalating into the cell membrane, altering the local lipid environment to hinder plaque formation [127].…”
Section: Gap Junction Channel Inhibitors (Fig 2)mentioning
confidence: 99%